2020
DOI: 10.1002/14651858.cd011779.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the implementation of healthy eating, physical activity and obesity prevention policies, practices or programmes within childcare services

Abstract: Strategies to improve the implementation of healthy eating, physical activity and obesity prevention policies, practices or programmes within childcare services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 130 publications
2
82
0
Order By: Relevance
“…These include reaching children and families at greatest risk for developing obesity and related health-compromising conditions, implementing interventions that are easily integrated into existing structures, and providing children with fun and easy experiences that promote interest in, initiation, and maintenance of, healthy habits to last a lifetime. Previous research has reported that throughout the entire day, the place and time where the child is least physically active is in the ECEC [60,[81][82][83][84][85]; yet, there has been modest attention to promoting physical activity among younger children in this setting and the quality of the existing limited evidence is low [86]. ECEC classrooms and teachers face challenges with keeping children safe throughout the day; thus, many classroom strategies for maintaining order involve sedentary time, with the notable exception of unstructured play time out of doors.…”
Section: Discussionmentioning
confidence: 99%
“…These include reaching children and families at greatest risk for developing obesity and related health-compromising conditions, implementing interventions that are easily integrated into existing structures, and providing children with fun and easy experiences that promote interest in, initiation, and maintenance of, healthy habits to last a lifetime. Previous research has reported that throughout the entire day, the place and time where the child is least physically active is in the ECEC [60,[81][82][83][84][85]; yet, there has been modest attention to promoting physical activity among younger children in this setting and the quality of the existing limited evidence is low [86]. ECEC classrooms and teachers face challenges with keeping children safe throughout the day; thus, many classroom strategies for maintaining order involve sedentary time, with the notable exception of unstructured play time out of doors.…”
Section: Discussionmentioning
confidence: 99%
“…A closed-ended survey (see Appendix; available online at www.liebertpub.com/chi) was developed based on the updated CACFP meal pattern standards and prior child day care/early child care nutrition-related surveys, [8][9][10][24][25][26][27][28] input from nutrition and ECE experts, and following cognitive interviews (CIs) to test question wording and format 29,30 with center directors at eight CACFP child day care centers located in Illinois and Florida where two of the study authors reside. The University of Illinois at Chicago's Institutional Review Board approved a claim of exemption for the study (protocol #2017-0549).…”
Section: Survey Development and Administrationmentioning
confidence: 99%
“…Several Cochrane Reviews have highlighted the need for further research in this area. 13,[24][25][26] To fill the existing gap and to examine the emerging role of physical activity for cardiovascular health in early childhood, we conducted a cluster-randomized controlled trial in preschools in the City Hamburg, Germany. The aim of the present study was to assess the effectiveness of a physical activity intervention on hemodynamic and anthropometric variables as well as on physical activity levels and motor skill performance in 3-to 6-year-old children.…”
Section: Introductionmentioning
confidence: 99%